The Relevance of Science In The Ibañez´s Educational Counter-Reform (1929-1930): A Look at The Role of Girls in The School Press - Ramírez, Verónica; Leyton, Patricio (Revista de Historia Social y de las Mentalidades, 2024)
This article analyses how schoolgirls appropriated science in the context of Ibáñez’s Educational Counter-Reform (1929-1930), which prioritized teaching science following the Progressive Education model. We study the magazines and newspapers produced by schoolgirls throughout the country, which multiplied thanks to educational reforms that promoted the active participation of students in their formative processes. We conclude that, on the one hand, the schoolgirls became protagonists of the educational policies implemented during this period, and on the other, that the reforms encouraged the involvement of girls in scientific subjects and the development of specific areas of knowledge.
Keywords: Women; Science; School Newspapers; Press; Educational Reforms